Analisis Strategi Bersaing PT. Bank Central Asia, Tbk. Pada Kredit Perumahan - , Andhika Tirta Purnama, SE. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is aimed to analyze business strategies, strengths, weaknesses, threats and opportunities of PT Bank Central Asia Tbk (BCA) in the competition of banking industry sector. This research uses descriptive analytical method and using qualitative data analysis based on Porter's Five Forces and key success factors (KSFs). Results of data analysis formulated in the SWOT matrix. The research shows that strength factors of BCA are good financial performance, good management, good credit policy, operations and extensive network, and good human resource development. While weaknesses of BCA are lack of credit infrastructure and product image for upper middle class. Opportunity factors for BCA are high demand for home loan, changes in technology, increasing needs for housing and rising home loan market. Threat factors are the global economic fluctuation and strong competition in the banking industry. Key success factors for BCA are to be considered in order to survive in the future include good image and reputation, human resources skills, the ability of product innovation, operational effectiveness and extensive distribution channels.